Editors’ Note - Alberto Raposo; Cleber Corrêa (Journal on Interactive Systems)
In this issue, we start the 10th year of JIS. Throughout these years, JIS moved from a virtual and augmented reality publication to a more multidisciplinary scope, including related areas such as games and human-computer interaction. This current issue, particularly, is a very good example of this multidisciplinary characteristic of JIS. It includes five regular submissions that address themes such as participatory design, serious games for the elderly, gestural recognition, augmented reality, among others.